Cerebrospinal fluid analysis in the HIV infection and compartmentalization of HIV in the central nervous system - Sérgio Monteiro de Almeida (Arquivos de Neuro-Psiquiatria, 2015)
The nervous system plays an important role in HIV infection. The purpose of this review is to discuss the indications for cerebrospinal fluid (CSF) analysis in HIV infection in clinical practice. CSF analysis in HIV infection is indicated for the diagnosis of opportunistic infections and co-infections, diagnosis of meningitis caused by HIV, quantification of HIV viral load, and analysis of CNS HIV compartmentalization. Although several CSF biomarkers have been investigated, none are clinically applicable. The capacity of HIV to generate genetic diversity, in association with the constitutional characteristics of the CNS, facilitates the generation of HIV quasispecies in the CNS that are distinct from HIV in the systemic circulation. CSF analysis has a well-defined and valuable role in the diagnosis of CNS infections in HIV/AIDS patients. Further research is necessary to establish a clinically applicable biomarker for the diagnosis of HIV-associated neurocognitive disorders.